Pembiayaan Mikro Syariah dan BMT (Baitul Mall Wat Tamwil) - Rahmat Rafli; Nasrullah Bin Sapa; Rahman Ambo Masse (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Islamic microfinance is an important instrument in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) by providing access to capital in accordance with Islamic principles. This paper aims to explain the concept of Islamic microfinance, the definition and functions of Baitul Maal wat Tamwil (BMT), the financing products offered, and the socio-economic role of BMT in society. The study employs a literature review method by examining various relevant references related to Islamic microfinance and BMT. The findings indicate that Islamic microfinance operates based on the principles of justice, partnership, and the prohibition of usury (riba) through contracts such as mudharabah, musyarakah, murabahah, ijarah, and qardhul hasan. As an Islamic microfinance institution, BMT performs two primary functions: a social function (baitul maal) through the management of zakat, infaq, sadaqah, and waqf funds, and a business function (baitut tamwil) through the collection and distribution of funds to the community. The presence of BMT plays a significant role in improving access to financing for MSMEs, reducing dependence on moneylenders, promoting economic equity, and enhancing community welfare through Sharia-based economic empowerment programs. Therefore, BMT serves as a strategic instrument in strengthening the Muslim community’s economy and fostering equitable economic development.